Comparing the Relative Reactivities of Structurally Varied Alcohols toward Electrochemically Generated Superoxide. Issue 4 (14th December 2017) - Lauw, Sherman J. L.; Chiang, Zhong; Lee, Jazreen H. Q.; Webster, Richard D.
Abstract: Superoxide (O2 .− ) is a free‐radical anion of the reactive oxygen species (ROS) family. In the present study, the relative reactivities of 14 structurally varied aliphatic alcohols toward electrochemically generated O2 .− were investigated in solutions of N, N ‐dimethylformamide by using cyclic voltammetry (CV). Upon the stepwise addition of each substrate, the chemical reversibility of the one‐electron voltammetric reduction of the dioxygen (O2 ) to O2 .− was found to decrease, which enabled the extent of radical inhibition to be determined by measuring the resultant oxidative peak current ( I pa ) magnitudes on the reverse scan of the CV. Based on the electrochemical responses gathered, best fit plots of the percentage decrease in the anodic peak current (%Δ I pa ) against the concentration of substrate added were obtained and compared according to the different classes of alcohols that were examined (linear, fluorinated, branched, and poly‐hydroxylated). In addition, different parameters, such as electronic effects, steric effects, degree of hydroxylation, and kinetic effects that affect the O2 .− scavenging abilities of the alcohols, are also discussed. Abstract : Superoxide and alcohols : Cyclic voltammetry is used to generate O2 and examine its interaction with structurally varied aliphatic alcohols in dimethylformamide solutions. Based on the results obtained, general correlations between their structures (electronic or steric effects) and relative reactivities are also made.